Prevalence and Epidemiology of Apple Powdery Mildew in Northwest Himalayan Region of Himachal Pradesh - Neg, Renu; Tomar, Manica; Bhandari, Durga Prasad; Thakur, Rajneesh; Sharma, Shakshi (International Journal of Economic Plants, 2024)
A survey was conducted to assess the incidence and severity of powdery mildew of apples during April to July of 2020 and 2021 at the different locations of Kinnaur district, Himachal Pradesh, India. Assessment scale of Hofer et al. (2019) with slight modification was used for cultivar screening. Apple seedlings were grown in the pots in the polyhouse of the Department of Plant Pathology in order to test the pathogenicity of Podosphaera leucotricha. Pathogenicity was confirmed through inoculation tests by gently pressing diseased leaves on young leaves of five asymptomatic, potted one-year-old Gale Gala seedlings of apple. Five non-inoculated plants were used for a control treatment. Overall, twenty different apple cultivars were screened against powdery mildew planted under field conditions at Krishi Vigyan Kendra Sharbo, Kinnaur, Himachal Pradesh, India. Out of these cultivars, five cultivars viz. Red Delicious, Royal Delicious, Red Velox, Auvil Early Fuji and Oregon Spur II, were found to be less susceptible to Podosphaera leucotricha, causing powdery mildew of apples, while Granny Smith, Golden Delicious, and Gale Gala were found extremely susceptible. Gala series of cultivars were found to be extremely susceptible to the pathogen. Incidence of the disease ranged from 25.42% to 53.80% and severity from 39.75% to 66.25%, respectively. According to the present study the disease initiated during the first week of May and peaked in the month of July in district Kinnaur. Temperatures between 18–24°C and RH between 50–65% were found to be favourable for the disease development. The conditions in the region were found to favourable for disease development and spread.